3D Printing for STEAM Education - Zapata, Mireya (2022)
3D printing has been considered a disruptive technology and its impact on education with the generation of educational resources that increase student engagement and improve STEAM learning by promoting their creativity, collaborative work, attention and participation in class, strengthening the development of their skills. This paper discusses the different applications that can be given to rapid prototyping through 3D printing in education and how it can influence the STEAM skills acquired by students.